(untitled) (Global Journal of Management and Business Research, 2022)
The effect of education on health has increased over the last decades. This paper investigates the effect of the maternal education on antenatal care use. Based on the behavioural model and regression analyses with ordered multinomial logit model. We test this hypothesis using data from the Mics survey, 2010 on the CAR. In terms of results, we find that an additional year increases, other things being equal, the probability of making all visits by 2.14 times. We find that more educated mothers have a greater advantage in using more prenatal health care during pregnancy